RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays saccharata Sturt L .) PADA SISTEM OLAH TANAH DAN PESTISIDA NABATI - Sutra A Said; Fitriah Suryani Jamin; Hasna Dama; Indriati Husain; Suyono Dude (Program Studi Agroteknologi, Fakultas Sains dan Teknologi, Universitas Muhammadiyah Siddenreng Rappang, 2026)
Sweet corn (Zea mays saccharata Sturt L.) is a horticultural commodity with high economic value and broad development prospects in Indonesia. However, its production still faces several constraints, including declining productivity due to suboptimal cultivation practices and disturbances from plant pests. This study aimed to evaluate the effects of tillage systems and botanical pesticides, as well as their interaction, on the growth and yield of sweet corn. The research was conducted in Matinan Village, Gadung District, Buol Regency, Central Sulawesi Province. The experiment employed a factorial randomized block design with two factors. The first factor was the tillage system, consisting of two levels: no-tillage (NT) and minimum tillage (MT). The second factor was botanical pesticide application, consisting of three levels: no pesticide (control), 100 mL/L papaya leaf extract (P1), and 100 mL/L soursop leaf extract (P2). The results showed that both tillage systems, no-tillage and minimum tillage, had no significant effect on the growth and yield of sweet corn, including plant height, number of leaves, leaf area, flowering percentage, ear length, and fresh weight of 100 seeds. The application of botanical pesticides made from papaya and soursop leaf extracts also had no significant effect on all observed parameters. Keywords: botanical pesticide; growth; minimum tillage; no-tillage; sweet corn